2017
DOI: 10.1177/0269215517714830
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a modified wheelchair arm-support to reduce shoulder pain in stroke patients

Abstract: Objective:To evaluate the effect of modified wheelchair arm-support to mitigate hemiplegic shoulder pain and reduce pain frequency in stroke patients.Design:A single-blind randomized controlled trial using computer-generated simple randomization.Setting:Participants recruited from inpatients at the Guangdong Provincial Hospital of Chinese Medicine.Subjects:A total of 120 patients with stroke were divided into two groups.Interventions:All subjects underwent basic rehabilitation training and wheelchair assistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…These include participation based therapy ( 290 294 ), quality of life centered care ( 240 , 295 310 , 345 ), community based rehabilitation ( 311 315 ), home based rehabilitation ( 132 , 193 , 316 335 ), self-management ( 336 , 337 ), family or care giver-led training ( 340 342 , 350 , 353 , 354 ), telerehabilitation ( 317 , 343 , 346 , 349 ), and early therapy/rehabilitation ( 174 , 338 , 339 , 347 , 348 , 351 , 352 , 355 , 356 ).…”
Section: Resultsmentioning
confidence: 99%
“…These include participation based therapy ( 290 294 ), quality of life centered care ( 240 , 295 310 , 345 ), community based rehabilitation ( 311 315 ), home based rehabilitation ( 132 , 193 , 316 335 ), self-management ( 336 , 337 ), family or care giver-led training ( 340 342 , 350 , 353 , 354 ), telerehabilitation ( 317 , 343 , 346 , 349 ), and early therapy/rehabilitation ( 174 , 338 , 339 , 347 , 348 , 351 , 352 , 355 , 356 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hemiplegic shoulder pain (HSP) is a common and disabling complication following a stroke, and it may affect the quality of life [ 1 ]. It often occurs following two to three months of stroke [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It often occurs following two to three months of stroke [ 2 , 3 ]. Consequently, HSP may result in withdrawal from rehabilitation programs, longer hospital stays, reduced limb movement, and impaired quality of life [ 1 ]. Numerous causes have been implicated in developing HSP in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is followed by different complications, such as reduced physical activity (4), reduced life quality (5), and increasing pain (6). Pain is one of the most important problems in elderly and patients with stroke, which causes a lot of problems for this group of people (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with stroke experience different types of pain, including headaches, shoulder pain, and central post-stroke pins (13). Hemiplegic pain is one of the types of pain in patients with stroke, with an estimated prevalence of 16% to 84% (7,14,15). Also, in the study by Mazzocato et al 69% of patients had pain (16), and in a review article by de Vries et al it was shown that between 87.3% and 87.8% of patients experienced pain, indicating the importance of pain in these patients (17).…”
Section: Introductionmentioning
confidence: 99%